Physical properties of matured pepper berries - Megat Ahmad Azman, Puteri Nurain; Shamsudin, Rosnah; Che Man, Hasfalina; Ya'acob, Mohammad Effendy (Malaysian Society of Agricultural Engineers, 2019)
Pepper is known as the ‘King of Spices’ and its botanical name is Piper Nigrum which is one of the most popular and oldest spices in the world. There is a problem during manual sorting and grading of pepper such as the selected pepper berries for white pepper production are less fulfilled according to standard of properties (dimension, weight and colour) requirement that had been done by man power. This study is carried out to determine the physical properties (dimension, weight, and colour) of mature pepper berries because they are vital in sorting and grading to evaluate the food quality. The physical properties of food materials is essential for processing design and optimization. The preparation of the samples is starting to collect from the plantation. The spikes with mature pepper berries were threshed manually to obtain the pepper berries. The only full mature pepper berries were selected and prepared for further analysis. The physical properties of mature pepper berries such as dimension (5.42 mm), weight (0.12 g), and colour (value of 63.05 (a*), 47.33 (b*), and 39.17 (L*)) were obtained after analysed. Hence, the results are based on the maturity period and can be applicable for the food processing.